Phase II study of olaratumab with paclitaxel/carboplatin (P/C) or P/C alone in previously untreated advanced NSCLC. (September 2017) - Gerber, David E.; Swanson, Paul; Lopez-Chavez, Ariel; Wong, Lucas; Dowlati, Afshin; Pennell, Nathan A.; Cronier, Damien M.; Qin, Amy; Ilaria, Robert; Cosaert, Jan; Shahir, Ashwin; Baggstrom, Maria Q.
Highlights: Olaratumab (IMC-3G3) is a fully human anti-PDGFR monoclonal antibody. Olaratumab plus carboplatin-paclitaxel does not prolong PFS or OS in NSCLC. PDGFR expression is rare in NSCLC tumor cells but common in NSCLC stroma. The addition of olaratumab to chemotherapy is well tolerated. Abstract: Background: In non-small cell lung cancer (NSCLC), platelet-derived growth factor receptor (PDGFR) mediates angiogenesis, tissue invasion, and tumor interstitial pressure. Olaratumab (IMC-3G3) is a fully human anti-PDGFRα monoclonal antibody. This Phase II study assessed safety and efficacy of olaratumab + paclitaxel/carboplatin (P/C) versus P/C alone for previously untreated advanced NSCLC. Materials and methods: Patients received up to six 21-day cycles of P 200 mg/m 2 and C AUC 6 (day 1) ± olaratumab 15 mg/kg (days 1 and 8). Primary endpoint was PFS. Olaratumab was continued in the olaratumab + P/C arm until disease progression. Results: 131 patients were: 67 with olaratumab + P/C and 64 with P/C; 74% had nonsquamous NSCLC. Median PFS was similar between olaratumab + P/C and P/C (4.4 months each) (HR 1.29; 95% CI [0.86–1.93]; p  = 0.21). Median OS was similar between olaratumab + P/C (11.8 months) and P/C (11.5 months) (HR 1.04; 95% CI [0.68–1.57]; p  = 0.87). Both arms had similar toxicity profiles. All evaluable cases were PDGFR-negative by immunohistochemistry. Tumor stroma PDGFR expression was evaluable in 23/131 patients, of which 78% were positive. Conclusions: The addition of olaratumab to P/C did not result in significant prolongation of PFS or OS in advanced NSCLC. Olaratumab studies in other patient populations, including soft tissue sarcoma (NCT02783599), pancreatic cancer (NCT03086369), and pediatric malignancies (NCT02677116) are underway.